PENURUNAN KANDUNGAN BENZO(A)PIRENA ASAP CAIR HASIL PEMBAKARAN - Fatimah, Feti; Gugule, Sanusi (Sam Ratulangi University, 2009)
This research was done to study benzo(a)pirene content produced from liquid smoke by directburning process, also how to reduced the component. The results show that liquid smoke from coconutpericarb that produced by direct burning method has 28% recovery. The smoke was yellow to brown,smelled as smoke with density 0,9965 g/mL. To reduce benzo (a) pirene of liquid smoke was done usingredistilled and absorbed with active carbon. Redistilled liquid smoke was done at 98-100 oC. RedistilledLiquid smoke almost colorless and no color compared with initial liquid smoke, less smoke scent. Thedensity was 0,9970 g/mL with 55% recovery from initial smoke. Absorbed liquid smoke using activecarbon (1:5) was acquired more clear liquid, no color and no scent, density 0,9975 g/mL with 51,7%recovery. Benzo(a)pirene concentration can be reduced using redistilled and absorbed with activecarbon method. Reduce concentration using redistilled technique was 33.1%, whereas using absorbedtechnique was 54,3%.